O projeto de educação popular e desenvolvimento comunitário da Arquidiocese de Fortaleza em Carqueija, município de Capistrano - 1965 a 1975 - Alves, Francisco Artur Pinheiro (1993)
This study intends to rescue the memory of a Project of Community Development and Popular Education experienced from 1965 to 1975 by the community of Carqueija in Capistrano, Ceará. The historic reconstitution of the Project was made possible through testimony of former members, using the method of Oral History. It was also analysed a number of documents and photographs to supplement the list of documental sources. This study is divided into five chapters. The first chapter deals with the research methodology. The second is dedicated to the area where the project takes place, highlighting the principal characteristics of the region. The third analyses the different associate groups and the work union which played an important role in the Carqueija Project. The fourth chapter favors Formal Education. The fifth chapter makes some considerations concerning the playful side of the project, registering the artistic manifestation of entertainment in the community. The six chapter includes some of the main photographs of the project, which show the leaders and some important moments of the Project. This work is proceded by an introduction that indicates the general guide lines and introduces some questions about the theme. At the end in the chapter Conclusion there are some considerations about the studied subject. This work is a small contribution to the bibliography of Regional Popular Education and to the local history.